2002
DOI: 10.1111/j.1572-0241.2002.05534.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Gi Lesions in 241 Women With Iron Deficiency Anemia

Abstract: Endoscopy revealed a source of IDA in 49.4% of cases. Three predictive factors of GI lesion were identified. Endoscopic investigation should be avoided in women without these three predictive factors. Conversely, these factors are strongly associated with a GI lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 16 publications
3
29
3
Order By: Relevance
“…The prevalence of benign and malignant colorectal tumors (13% and 3%, respectively) was similar to other studies [10]. Furthermore the frequency of inflammatory GI lesions such as gastritis and esophagitis was more prevalent than GI ulcers and tumor lesions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of benign and malignant colorectal tumors (13% and 3%, respectively) was similar to other studies [10]. Furthermore the frequency of inflammatory GI lesions such as gastritis and esophagitis was more prevalent than GI ulcers and tumor lesions.…”
Section: Discussionsupporting
confidence: 72%
“…Endoscopic evaluation should not be done in women without predictive factors; abdominal symptoms, age > 50yrs, and Hb < 9g/dl. Conversely, these factors are strongly associated with a GI lesion [10,11].…”
Section: Research Articlementioning
confidence: 97%
“…This was similar to our result that more severe anemia (or lower serum ferritin level) also implied a greater chance for malignancy. Nahon et al [13] have reported age as a predictive factor of GI lesions in postmenopausal women with IDA. This was similar to our result that every increase of 1 year in age resulted in a risk of malignancy that was 1.062 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of the GI tract causing iron deficiency by mechanisms of bleeding or iron malabsorption were reported in 12-95% of this population [2][3][4][5][6]. The information regarding the predictive value of GI symptoms on the incidence of GI findings in premenopausal women is limited; prior studies did not evaluate thoroughly IDA patients with and without symptoms.…”
Section: Introductionmentioning
confidence: 93%